2015
DOI: 10.1007/s00253-015-6560-y
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae EC-1118 enhances the survivability of probiotic Lactobacillus rhamnosus HN001 in an acidic environment

Abstract: The present study attempted to partially characterize and elucidate the viability-enhancing effect of a yeast strain Saccharomyces cerevisiae EC-1118 on a probiotic strain Lactobacillus rhamnosus HN001 under acidic conditions using a model system (non-growing cells). The yeast was found to significantly enhance (P < 0.05) the viability of the probiotic strain under acidic conditions (pH 2.5 to 4.0) by 2 to 4 log cycles, and the viability-enhancing effects were observed to be influenced by pH, and probiotic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Therefore, the objective of this pilot study was to investigate the influence of three commercial IYDs that are rich in yeast parietal molecules on the survival of a widely used probiotic bacteria strain, Lactobacillus rhamnosus HN001, in a simulated acidic environment (buffer). As the IYDs studied are derived from S. cerevisiae of oenological origin, the findings of this study could also shed light on the survival-enhancing properties of non-viable S. cerevisiae EC-1118 cells on L. rhamnosus HN001 as previously reported by Suharja et al (2014) and Lim et al (2015). …”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Therefore, the objective of this pilot study was to investigate the influence of three commercial IYDs that are rich in yeast parietal molecules on the survival of a widely used probiotic bacteria strain, Lactobacillus rhamnosus HN001, in a simulated acidic environment (buffer). As the IYDs studied are derived from S. cerevisiae of oenological origin, the findings of this study could also shed light on the survival-enhancing properties of non-viable S. cerevisiae EC-1118 cells on L. rhamnosus HN001 as previously reported by Suharja et al (2014) and Lim et al (2015). …”
Section: Introductionsupporting
confidence: 73%
“…An acid stress assay, modified from the method of Lim et al (2015), was used to assess the impact of IYDs on the survival of L. rhamnosus HN001 in an acidic buffer. Twenty mL of L. rhamnosus HN001 working culture was mixed with an equal volume of IYD extract (giving a final IYD concentration of 3 g/L or 0.3% (w/v)) or pH 3.0 PBS for the control in a 50-mL polypropylene centrifuge tube and incubated statically in a 30 °C incubator for 10 h. As viable S. cerevisiae EC-1118 cells were demonstrated to enhance the viability of L. rhamnosus HN001 under similar stress conditions, an assay comprising of equal volumes probiotic bacteria and yeast working cultures was also performed for comparing the IYDs’ probiotic viability enhancing effect (Lim et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…has inhibitory activity against Streptococcus mutans, and Streptococcus sobrinus, etiological agents strongly associated with dental cavities in humans (112). Lim et al (2015) showed that some yeast increase the growth of other probiotics under acidic conditions, like Saccharomyces cerevisiae CE-1118, that improves the viability of the probiotic Lactobacillus rhamnosus HN001 under pH 2.5-4 (113).…”
Section: Probiotics Therapeutic Applicationsmentioning
confidence: 99%